2008
DOI: 10.1029/2008ja013513
|View full text |Cite
|
Sign up to set email alerts
|

Wind dynamo effects on ground magnetic perturbations and vertical drifts

Abstract: [1] The equatorial electrojet (EEJ) flows as an enhanced eastward current in the daytime E region ionosphere between 100 and 120 km height at the Earth's magnetic equator. The flowing currents in the ionosphere induce magnetic perturbations on the ground. Calculating the difference between the horizontal components of magnetic perturbation (H) at magnetometers near the equator and about 6-9 degrees away from the equator, DH, provides us an indicator of the strength of the EEJ. However, in this research we show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 47 publications
0
37
1
Order By: Relevance
“…Scherliess and Fejer 1999) Equatorial daytime vertical drifts are also now routinely derived from the difference of horizontal geomagnetic fields measured at pairs of stations, one very near the magnetic equator and another a few degrees off at about the same longitude (e.g., Anderson et al 2002Anderson et al , 2004Shume et al 2009). Vertical drifts derived using magnetic field data from Jicamarca and Piura (5.2°S, 80.6°W; 6.8°magnetic) are generally in good agreement with radar measured 150-km and F region Jicamarca drifts, but their accuracy can sometimes be affected by magnetic field changes produced by variable low latitude E region winds (e.g., Fang et al 2008). Recently, equatorial zonal electric fields have been derived from equatorial magnetic field measurements by the CHAMP satellite (Alken and Maus 2010).…”
Section: Climatology Of Equatorial Plasma Driftsmentioning
confidence: 84%
“…Scherliess and Fejer 1999) Equatorial daytime vertical drifts are also now routinely derived from the difference of horizontal geomagnetic fields measured at pairs of stations, one very near the magnetic equator and another a few degrees off at about the same longitude (e.g., Anderson et al 2002Anderson et al , 2004Shume et al 2009). Vertical drifts derived using magnetic field data from Jicamarca and Piura (5.2°S, 80.6°W; 6.8°magnetic) are generally in good agreement with radar measured 150-km and F region Jicamarca drifts, but their accuracy can sometimes be affected by magnetic field changes produced by variable low latitude E region winds (e.g., Fang et al 2008). Recently, equatorial zonal electric fields have been derived from equatorial magnetic field measurements by the CHAMP satellite (Alken and Maus 2010).…”
Section: Climatology Of Equatorial Plasma Driftsmentioning
confidence: 84%
“…Immel et al (2006) conclude that neutral winds in the lower atmosphere influence and modulate the E-region dynamo to produce spatial variability approximately 1,000 km scales. Other causes of EEJ variability suggested by earlier workers are (i) the variations in tidal strength (Stening 1975) and the sharp longitudinal gradients in the diurnal non-migrating tides (DE2 and DW2) between the longitudes over 15°separation (Anderson et al 2009); (ii) the day to day variability of zonal winds (Fang et al 2008); (iii) the day-to-day variability in semidiurnal tide at lower thermosphere, modulated by interactions at planetary wave periodicities (Fuller-Rowell et al 2008); and (iv) the modulation of ionospheric dynamo in the middle atmosphere through the excitation of solar non-migrating tides in the troposphere (Jin et al 2011).…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that Sq and EEJ are driven by different factors, which could naturally result in a weak correlation between the two. Fang et al (2008) has demonstrated using a Thermosphere Ionosphere Mesosphere Electrodynamic General Circulation Model (TIME-GCM) simulation that local wind could significantly affect the EEJ. We also know that Sq is affected by large-scale global wind, while EEJ is affected by both global and local wind.…”
Section: Discussionmentioning
confidence: 99%